ANALISIS PELUANG DAN TANTANGAN PERBANKAN SYARIAH DI ERA DIGITAL - Muhammad Ash Shiddiqy (JASIE, 2023)
The development of the digital era has made all sectors including Islamic banking required to digitize. Coupled with the existence of Digital Financial Innovation (IKD), Islamic banks must participate in this transformation so they are not left behind. Therefore, it is important to study the prospects for future development of the Islamic economy, by looking at the opportunities and challenges faced by Islamic banks in order to survive and continue to develop in the current era of digitalization. The research method in this article is descriptive qualitative. The results of the analysis are first, Islamic banking is one of the organizers of a new business model known as